1962
DOI: 10.1172/jci104572
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies of the Gamma-Related Proteins of Normal Urine

Abstract: The designation "gamma-related" will be applied to any protein antigenically related to-i.e., reacting with antiserum prepared against-human plasma y-globulins.Webb, Rose and Sehon (1) and Franklin (2) have described the urinary proteins of y-electrophoretic mobility. They found that these consisted largely of material of lower molecular weight than, but antigenically related to, the 7S y-globulin of plasma. The protein population described in these two papers overlaps that defined in this and a previous paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
22
1
1

Year Published

1965
1965
1974
1974

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 21 publications
4
22
1
1
Order By: Relevance
“…This material contained the antigenic groupings I and II described in Bence Jones proteins and other immunoglobulins (31). This observation has also been reported by earlier investigators (6,8). However, our studies showed in addition that material antigenically related to H chains and F fragments of 7 S y-globulin was regularly found in small amounts in the YL-fraction.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…This material contained the antigenic groupings I and II described in Bence Jones proteins and other immunoglobulins (31). This observation has also been reported by earlier investigators (6,8). However, our studies showed in addition that material antigenically related to H chains and F fragments of 7 S y-globulin was regularly found in small amounts in the YL-fraction.…”
supporting
confidence: 91%
“…This has been described by other authors (6) and is apparent from the broad distribution of electrophoretic mobility and by the studies presented here in the gel filtration experiments.…”
supporting
confidence: 88%
See 3 more Smart Citations